A new Krakow scanning nuclear microprobe: performance tests and early application experienc - Lebed, S.; Lekki, J.; Paszkowski, M.; Polak, W.; Potempa, A.; Stachura, Z.; Styczen, J. (Вопросы атомной науки и техники, 2001)
A new scanning nuclear microprobe (MP) with a short-length probe forming system was designed, installed and tested at the 3MV Van de Graaff accelerator in Krakow. The MP resolution of 3.3mm was reached for a 2.4 MeV proton beam in the high-current mode (≥100pA). The MP facility provides a local, non-destructive, quantitative elemental microanalysis using a Proton Induced X-ray Emission (PIXE) technique. As example of possible applications an analysis of a geological sample containing monazite crystals investigated by PIXE method is presented.